Evaluation of Post-Bronchodilator Reversibility in Patient with Chronic Obstructive Pulmonary Disease and Asthma - Devkota, Krishna Chandra; Hamal, S; Pant, PP (Nepal Medical College Journal, 2020)
Obstructive lung disease is a group of disorders comprising Chronic Obstructive Pulmonary Disease (COPD) and asthma. It is one of the most common causes of morbidity and mortality worldwide. COPD is a preventable and treatable disease characterized by persistent respiratory symptoms and airflow limitation, whereas asthma is reversible episodes of recurrent wheezing, cough, breathlessness, and chest tightness. It is sometimes difficult to distinguish COPD from asthma when COPD patients present with significant post-bronchodilator reversibility. Spirometry is the gold standard test to diagnose obstructive airway disease. We carried out a hospital-based cross-sectional study in Nepal Medical College Teaching Hospital from January 2018 to December 2018. One hundred and ninety eight patients who met the inclusion criteria underwent spirometry. Basal and post-bronchodilator FEV1, FVC, FEV1/FVC, and reversibility of FEV1 were measured. The majority of the patients enrolled in the study were males (n=100). The mean age of the patients was 49.3±17.0 years. Most of the patients were above 60 years of age (n=68). Clinical diagnosis of asthma was made in 113 (57%) and COPD in 85 (43%) patients. Post-bronchodilator reversibility was observed in 48 (42%) asthmatic and 19 (22%) COPD patients. Post-bronchodilator reversibility was statistically significant in asthmatic patients (p=0.032). Post-bronchodilator reversibility was observed in COPD patients as well. Therefore, post-bronchodilator reversibility alone may have a limited role in differentiating COPD from bronchial asthma. However, spirometry is mandatory to diagnose a patient with obstructive lung disease.